TRADISI BUKA LUWUR DALAM PENGUATAN PENDIDIKAN KARAKTER ANAK SEKOLAH DASAR DI DESA KALIWUNGU - Nisa Indarti; Sri Utaminingsih; Sekar Dwi Ardianti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to analyze the implementation of the Buka Luwur Tradition in Kaliwungu Village and to find the character values contained in this tradition. This study used a descriptive qualitative method with a phenomenological approach. The object of this study was the Buka Luwur Tradition in Kaliwungu Village, while the subjects were the people of Kaliwungu Village. The targets of this study included caretakers of the tomb, administrators of the Buka Luwur Tradition, community leaders, the head of the RW, and elementary school children in Kaliwungu Village. The data were obtained through in-depth interviews, observation, documentation, and recording. The data sources in this study were the people and the elementary school children in Kaliwungu Village. The validity test applied the source triangulation technique. Then, the data were analyzed by data reduction, data presentation, and conclusions verification. The implementation of the Buka Luwur Tradition was marked by the release of